Comparative and Veterinary Pharmacology - Cunningham, Fiona; Elliott, Jonathan; Lees, Peter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The topics addressed in this volume of comparative and veterinary pharmacology, as a series of succinct state of the art reviews, illustrate both the commonality and differences between drug pharmacodynamics and pharmacokinetics in animals and man and demonstrate the potential impact of drug use in animals on human health and the environment. Genetic modification of animals and the benefits this has brought to understanding human disease and the production of drugs for use in man is considered and the potential of new technologies for improving the treatment of animal disease explored.
Part I: Topics in Veterinary Pharmacology -- Introduction. Species variability in pharmacokinetics and pharmacodynamics. Pharmacogenomics in domestic animal species. Drug delivery in domestic animal species. Population medicine and control of disease epidemics. Interspecies allometric scaling. Pain and analgesia in domestic animal species. New technologies for application to veterinary therapeutics -- Part II: The Interface of Veterinary Pharmacology and Man -- Genetically modified animal. Antimicrobial drug resistance. Drug residues. Veterinary medicines and the environment. Veterinary medicines and competition animals.
Keywords: Medicine; Drug interactions; Toxicology; Pain Medicine; Sports medicine; Veterinary medicine; Biomedicine; Pharmacology/Toxicology.; Veterinary Medicine; Medicine/Public Health, general; Drug Resistance; Pain Medicine; Sports Medicine